Functional single nucleotide polymorphisms in dopaminergic receptors D2 predict clinical response to Cariprazine - De Pieri, Marco; Ferrari, Marco; Marino, Franca; Traber, Rafael; Bolla, Emilio; Cosentino, Marco (Frontiers in Pharmacology, 2023)
Cariprazine (CAR) is an antipsychotic drug for the treatment of schizophrenia (SCZ) and bipolar disorder (BD), and it acts as a partial agonist on the dopamine receptors (DR), D2 and D3. Although many single nucleotide polymorphisms (SNPs) in genes coding for these receptors are known to influence response to antipsychotics, to date, no study on CAR pharmacogenetics exists. In this pilot study, we investigated the relationship between SNPs in DRD2 (rs1800497 and rs6277) and DRD3 (rs6280), and response to CAR treatment, evaluated by the psychometric Brief Psychiatric Rating Scale (BPRS), in a cohort of Caucasian patients. We found a significant association between DRD2 rs1800497 and rs6277 and response to CAR treatment. When genotypes were combined into an arbitrary score, the receiver operating characteristic curve analysis showed that using a cut-off value of -2.5 the response to CAR treatment could be predicted with a positive likelihood ratio of 8.0. Our study report, for the first time, a correlation between SNPs in DRD2 and response to CAR treatment. After confirmation in a larger cohort of patients, our results could open the way for the identification of new tools for the provision of response to CAR treatment.